'More likely to be killed by a coconut': varying professional perceptions of risk impacting residential development planning around pipelines. Issue 2 (1st February 2021) - Hayes, Jan; Sandri, Orana; Holdsworth, Sarah
Abstract: Best practice in land use planning linked to hazardous infrastructure requires that views of multiple stakeholders are considered. This study addresses the varying views of risk held by two groups of experts – pipeline sector engineers and land use planners – when it comes to decision making about residential development at the urban fringe near existing high pressure gas pipeline infrastructure. Given that third-party activities, particularly excavation, are the largest cause of pipeline failure, continuing urban expansion into historically rural areas poses a significant risk to high pressure pipelines. The serious fires or explosions that can result have the potential to impact any nearby communities. Consequently, land use planning decisions can have a direct impact on public safety near pipelines. Drawing on interviews with land use planners and pipeline sector engineers in Australia, the comparative analysis highlights the different perceptions of risk of these groups driven by differing views about how to frame the issue of new housing near existing pipelines. Current institutional structures foster a lack of trust. Better risk governance would result in less conflict between the various parties and hence better community outcomes for both safety and amenity. The study also demonstrates that risk research findings focused on hazardous facility siting does not translate directly into the converse case of residential development siting near industrial facilities. This case provides evidence of a broader need for risk research and land use planning to better address 'hazard creep' – where residential development moves into areas potentially impacted by existing hazardous facilities such as pipelines but also including dams and other kinds of infrastructure.